2016
DOI: 10.1007/s10802-016-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Findings from a National Effectiveness Trial: Effectiveness of Behavioral and Non-Behavioral Parenting Programs

Abstract: Long-term follow-up studies of selective parent training (PT) programs are scarce, particularly in the case of effectiveness trials conducted within regular care settings. This study evaluated the 2-year effects of 4 programs: Comet, Incredible Years, Cope, and Connect and differences in the rate of change among programs were investigated using Latent Growth Modeling (LGM). Participants were parents who had sought help at 30 local service sector units (e.g., child psychiatric clinics and social services center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
2
24
0
1
Order By: Relevance
“…This may be done without negative consequences for QoL, parenting stress, or comorbid symptoms, beyond ADHD symptoms at home and school and oppositional symptoms at school. While our study suggests beneficial effects of long-term methylphenidate use regarding oppositional symptoms, it should be noted that nonpharmacological treatment (i.e., parent training) may also lead to long-term improvement of oppositional behavior (Hautmann et al, 2009;Högström et al, 2017;Döpfner et al, 2018).…”
Section: Long-term Benefits Methylphenidate 163mentioning
confidence: 58%
“…This may be done without negative consequences for QoL, parenting stress, or comorbid symptoms, beyond ADHD symptoms at home and school and oppositional symptoms at school. While our study suggests beneficial effects of long-term methylphenidate use regarding oppositional symptoms, it should be noted that nonpharmacological treatment (i.e., parent training) may also lead to long-term improvement of oppositional behavior (Hautmann et al, 2009;Högström et al, 2017;Döpfner et al, 2018).…”
Section: Long-term Benefits Methylphenidate 163mentioning
confidence: 58%
“…18 Several studies indicate that nonbehavioral parenting programs might not yield a short-term effect. [30][31][32] By contrast, nonbehavioral programs that focus on strengthening parent-child relationships, particularly in older children, have been effective. 33 What differentiates the Connect program from others is that Connect focuses on parents building a partnership with their child and jointly solving conflicts, whereas other parenting programs focus on approving positive or disapproving negative behavior in children.…”
Section: Discussionmentioning
confidence: 99%
“…Parental report of child behaviour problems were collected at baseline, 4 months after the baseline (post-test) and at a 2-year follow-up. The waitlist control was only allowed for 4 months due to ethical considerations, therefore the 2-year follow-up only serves as an indication of the maintenance of the interventions' effectiveness (Högström et al 2017). Due to difficulties in finding cost data for children below the age of five with behaviour problems, we included data from children aged 5-12 and excluded children aged 3-4.…”
Section: Data Collection From the Original Trialmentioning
confidence: 99%
“…Parenting programs are a recommended approach for primary, secondary and tertiary prevention of behaviour problems in Sweden and are delivered in 85% of all local authorities (The National Public Health Institute of Sweden 2013). A six arm randomised controlled trial evaluated some of the most commonly used parenting programs in Sweden and found that almost all are effective at reducing behaviour problems in the short-term (Stattin et al 2015) and maintain these reductions in the longer-term (Högström et al 2017). In addition, economic evidence of the short-term results indicate that most are cost-effective (Sampaio et al 2016).…”
Section: Introductionmentioning
confidence: 99%